Gasification of lignin-rich residues for the production of biofuels via syngas fermentation: Comparison of gasification technologies. (1st September 2019) - Liakakou, E.T.; Vreugdenhil, B.J.; Cerone, N.; Zimbardi, F.; Pinto, F.; André, R.; Marques, P.; Mata, R.; Girio, F.
Abstract: This paper reports the use of lignin-rich residues from second generation bioethanol production, to produce syngas that can be applied in the gas fermentation process. Three gasification technologies at a different scale were considered in this study. Fixed bed updraft gasification of about 30 kg/h solid feed, bubbling fluidized bed gasification of about 0.3 kg/h solid feed and indirect gasification of about 3 kg/h solid feed. Two lignin-rich residues with different properties were tested and the results were evaluated in terms of feedstock pretreatment (grinding, drying and pelleting) and syngas quality requirements for the fermentation process. The molar H2 /CO ratio (ranging from 0.6 to 1.0) and the tar yield (18–108 g/Nm 3 ) obtained from the three gasification technologies was quite different. For the syngas fermentation process, low H2 to CO ratio is preferred, as most of the organisms grow better on CO than H2 . Furthermore, different contents of impurities that can reduce the fermentability of the gas (such as hydrocarbons, HCN, HCl, NH3, COS and other organic S- compounds) were detected in the product gas. The concentration of these compounds in the syngas is related to the content of the corresponding compounds in the original feedstock. The different characteristics of the lignin-rich feedstocks are related to the specific pre-treatment technologies for the (hemi)cellulose extraction. By tuning the pre-treatment technology, the properties of the feedstock can be improved, making it a suitable for gasification. Tar and unsaturated hydrocarbon compounds need to be removed to very low levels prior to the fermentation process. As a next step, the combination of the gasification and the appropriate product gas cleaning, with the syngas fermentation process for the production of bio-alcohols will be evaluated and the overall efficiency of the gasification-fermentation process will be assessed.